Estymacja premii za ryzyko na podstawie ROE - Kurek, Bartosz (Risk Premium Estimation on the Basis of Roe, 2005)
The paper presents the proposal of risk premium estimation based on Return of Equity (ROE) index. In order to prove the thesis, empirical research in banking sector in Poland has been conducted. ROE indices of the banks listed on the Warsaw Stock Exchange during a period of 1991-2003 have been taken into consideration. The result from the research confirms the outcome of the computations of "beta" index in the Capital Asset Pricing Model and risk factor in Arbitrage Pricing Theory of banking sector in the USA. As a conclusion the banking sector in Poland can be characterized as average risk level one.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 222-231